Substitutions in Nd5−xTbxMo3O16+δ Series: Phase Formation, Atomistic Modeling, and Crystal Structure of Nd5Mo3O16+δ-Based Solid Solutions - Konstantin A. Chebyshev; Nelly I. Selikova; Lyudmila V. Pasechnik; A. V. Ignatov (Journal of Chemistry, 2023)
Samples of the Nd5−xTbxMo3O16+δ series were obtained by solid-state synthesis from metal oxides at 1050°C. The formation of solid solutions based on cubic and monoclinic phases and a two-phase region between them was observed in the Nd5−xTbxMo3O16+δ compositions. Increasing the terbium content in the system leads to a decrease in the unit cell parameters of the cubic and monoclinic phases within their homogeneity regions, which confirms the formation of solid solutions. It has been established that the terbium oxidation state in the Nd5Mo3O16+δ crystal structure is +3. The predominant placement of terbium atoms in the 8c position is observed by crystal structure refinement and confirmed by the results of the atomistic simulation. The introduction of terbium into the crystal structure of neodymium molybdate leads to a decrease in the Ln1–O1 and Ln2–O2 interatomic distances. The atomistic simulation was performed by the GULP program using the fit potential of the terbium ion. Terbium molybdate with Tb5Mo3O16+δ composition is a subtraction solid solution based on Tb2MoO6. Increasing the unit cell parameters of Tb5Mo3O16+δ monoclinic phase compared to Tb2MoO6 was confirmed by structure refinement and atomistic simulation.